Biodiversity of semiarid landscape : baseline study for understanding the impact of human development on ecosystems /: baseline study for understanding the impact of human development on ecosystems. ([2015]) - Nautiyal, Sunil; Bhaskar, Katari; Khan, Y. D. Imran
No abstract available